Techniques and Economies in the Ancient Mediterranean - Jean-Pierre Brun (Collège de France, 2013)
Every age invents a new way of writing history, or at least seeks to shed light on the present by examining the past differently. For the past thirty years the amount of data produced by archaeology, especially by preventive excavations, has grown exponentially, thus opening new research perspectives on the history of ancient techniques and economies. Against a background of paucity of written sources, archaeology is currently producing series of documents enabling us to study the real state ...